New square-planar nickel(II)-triphenylphosphine complexes containing ONS donor ligands: Synthesis, characterization, electrochemical and antioxidant properties - KOCA, ATIF (ELSEVIER, 2020)
Five new mixed ligand nickel(II) complexes with the general formula [Ni(L)(PPh3)], [C1-C5], were prepared from the reaction of triphenylphosphine (PPh3) with ONS donor ligands (L) [where R = H (L1); 4-OCH3 (L2); 4-OCH2(CH2)(6)CH3(L3); 4-OCH3, 4'-CH3 (L4) and 4-OCH2CH=CH2(L5)] derived from 2-hydroxybenzophenones and thiocarbohydrazide. The structures of the complexes were characterized by elemental analysis, IR, H-1 and P-31 NMR spectroscopy, conductivity measurements. The crystal structures of ligand (L2) and complex (C2) were determined by single crystal X-ray diffraction method. The ligand is coordinated to the nickel core through the phenolate oxygen, azomethine nitrogen and sulfur atoms, while the fourth coordination site is occupied by the P atom of a triphenylphosphine ligand. X-ray analysis indicated distorted square-planar structure for the complex C2. Electrochemical behaviors of thiocarbohydrazone ligands (L1-L5) and their nickel(II) complexes (C1-05) were studied and effects of the type of substituents were compared. All ligands illustrated two irreversible reductions and one irreversible oxidation. Complexing of the ligands with Ni(III) ion considerably influenced their redox behaviors. Electron transfer process of the complexes get easier and became more reversible when compared with those of the corresponding ligands. Moreover, Ni(II) complexes illustrated Ni-II/Ni-I and Ni-II/Ni-III processes in addition to the ligand-based electron transfer reactions. In-situ spectroelectrochemical responses of the ligands considerably changed after formation of Ni(II) complexes. Total antioxidant capacity and free radical scavenging activity of the compounds have been tested using CUPRAC and DPPH methods, respectively. The results of Ni(II) complexes were compared with a standard antioxidant compound. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Thiocarbohydrazone; Nickel(II)-triphenylphosphine complex; Crystal structure; Electro-spectroelectrochemistry; Antioxidant capacity; TRANSITION-METAL-COMPLEXES; CRYSTAL-STRUCTURE; SPECTRAL CHARACTERIZATION; NICKEL(II) COMPLEXES; X-RAY; ORGANOTIN(IV) COMPLEXES; ANTIBACTERIAL ACTIVITY; CIS-DIOXOMOLYBDENUM(VI) COMPLEXES; STRUCTURAL-CHARACTERIZATION; ANTIMICROBIAL ACTIVITY